Validation of a scale based on the DigComp framework on internet navigation and cybersecurity in older adults - Rodríguez-Miranda, Francisco de Paula; Illanes-Segura, Rocio; Ceada-Garrido, Yolanda; Infante-Moro, Juan Carlos (Frontiers in Education, 2025)
The global COVID-19 pandemic revealed the persistence of the digital divide in older adults. The need to use technologies in order to communicate, remain informed and have contact with society, along with the need to perform online transactions, led to increased susceptibility, given the potential for scams and cyberattacks. This was a cause of concern amongst the general population, and especially amongst the elderly. The aim of this study is to validate a useful and reliable scale that measures the digital literacy of the senior population. This literacy refers to how they safely search for and manage information, as well as their competencies with regard to the security of their own devices. This scale was created through the adaptation of competencies 1.1, which consist of “browsing, searching and data filtering,” as well as 4.1, which considers “protecting devices,” from the DigComp model. The quantitative and qualitative analyses have required three samples: (1) a group of experts (N = 20) to adapt the scale to the Active Aging Model, (2) a group of older adults (N = 50) to carry out the exploratory factor analysis and (3) another group of older adults (N = 174) for the confirmatory factor analysis. The results of the analysis reveal the validity and reliability of the designed scale. To conclude, on one hand, the proposed model reveals a goodness of fit; on the other hand, older adults continue to demonstrate a reluctance to use the technologies for financial dealings. In this study, we present a new and reliable instrument adapted to the digital needs of seniors, which can be used by organizations and administrations to promote support policies and training activities for older adults within the active aging framework.